Uniqueness for measure-valued equations of nonlinear filtering for stochastic dynamical systems with Lévy noise. (26th July 2018) - Qiao, Huijie
Abstract: In the paper we study the Zakai and Kushner–Stratonovich equations of the nonlinear filtering problem for a non-Gaussian signal-observation system. Moreover, we prove that under some general assumption, the Zakai equation has pathwise uniqueness and uniqueness in joint law, and the Kushner–Stratonovich equation is unique in joint law.